Combination therapy with oncolytic viruses and immune checkpoint inhibitors. (2nd June 2020) - Chiu, Matthew; Armstrong, Edward John Lloyd; Jennings, Vicki; Foo, Shane; Crespo-Rodriguez, Eva; Bozhanova, Galabina; Patin, Emmanuel Christian; McLaughlin, Martin; Mansfield, David; Baker, Gabriella; Grove, Lorna; Pedersen, Malin; et al.
ABSTRACT: Introduction : Immune checkpoint inhibitors (ICI) have dramatically improved the outcome for cancer patients across multiple tumor types. However the response rates to ICI monotherapy remain relatively low, in part due to some tumors cultivating an inherently 'cold' immune microenvironment. Oncolytic viruses (OV) have the capability to promote a 'hotter' immune microenvironment which can improve the efficacy of ICI. Areas covered : In this article we conducted a literature search through Pubmed/Medline to identify relevant articles in both the pre-clinical and clinical settings for combining OVs with ICIs and discuss the impact of this approach on treatment as well as changes within the tumor microenvironment. We also explore the future directions of this novel combination strategy. Expert opinion : The imminent results of the Phase 3 study combining pembrolizumab with or without T-Vec injection are eagerly awaited. OV/ICI combinations remain one of the most promising avenues to explore in the success of cancer immunotherapy.